PENGARUH PEMBERDAYAAN PEGAWAI TERHADAP KUALITAS PELAYANAN PUBLIK DI KANTOR PELAYANAN WILAYAH UTAMA PERUSAHAAN DAERAH AIR MINUM (PDAM) TIRTA KHATULISTIWA PONTIANAK - Arfhi Ajudia E.42008035 (FISIP Universitas Tanjungpura Pontianak, 2012)
The purpose of this study is to investigate and analyze the effect of employeeempowerment on the quality of public services in the main area service office of PDAM TirtaKhatulistiwa Pontianak. This study was chosen because the authors see the phenomena and theproblems associated with the services provided. This problem is absolutely related to many factors,but the authors have alleged that good official empowerment factor will increase the maximumservice quality especially in serving the customers. This research uses quantitative perspective fortesting the hypothesis. The population in this study were all employees who work at the main areaservice office of PDAM Tirta Khatulistiwa Pontianak whose members is 20 employees. Theconclusion of this research is employee empowerment has a significant effect to the quality of public services by 37.3%. Therefore, quality of service will increase if ability and potentialservice providers are empowered as well as possible so it can resulting in maximum performance. Key Word : Empowerment, Quality of Public Services